Changes in pattern of complications in acute myocardial infarction over a ten-year follow-up: gender specificities - S. A. Okrugin; A. N. Repin (Кардиоваскулярная терапия и профилактика)
Aim. To compare changes in pattern of complications in acute myocardial infarction (MI) among Tomsk population at the age of >20 years over a ten-year follow-up period (2008-2017).Material and methods. The study was carried out on the basis of the World Health Organization Acute Myocardial Infarction Registry. In 2008, 800 MI cases were recorded (62,4% — men; 37,6% — women (p<0,001)). In 2017, acute MI was restarted in 906 patients (58,1% — men; 41,9% — women (p<0,05)). According to age pattern in 2008, there were 62,1% of patients >60 years of age (among men — 49,1%; among women — 83,7% (p<0,0001)), which after 10 years were 74,5 % (p<0,001).Results. In 2008, a complicated course of MI was observed in 49,9% of patients, in 2017, much more often — in 80,4% of patients (p<0,001). Over the analyzed period, incidence of acute aneurysm, myocardial rupture, and recurrent MI decreased. At the same time, the number of patients with post-MI heart failure (HF) significantly increased. In 2008, there were no significant differences in the incidence of MI complications in men and women. The most common complication in both men and women was arrhythmias and conduction disorders. After 10 years, the statistics remained virtually unchanged, with the exception of pulmonary embolism, which was significantly more common in women. Noteworthy is a significant increase in the number of HF patients (among men and women).Conclusion. Over a ten-year follow-up period, significant changes in patterns of MI complications in Tomsk were not revealed. It should be noted that MI became more severe and was more often accompanied by complications, the most common of which was HF. This is due to an increase in the age pattern of elderly and senile patients.